Eurasian Business Perspectives Proceedings of the 20th Eurasia Business and Economics Society Conference - Vol. 1 (Eurasian Studies in Business and Economics,, 2018)
This volume presents selected papers on recent management research from the 20th Eurasia Business and Economics Society (EBES) Conference, which was held in Vienna in 2016. Its primary goal is to showcase advances in the fields of accounting, auditing, marketing, and human resources in emerging economies. This volume is unique in its special focus on empirical research perspectives from countries such as Lithuania, Russia, and the Visegrád Group (the Czech Republic, Hungary, Poland and Slovakia), among others. .